3
$\begingroup$

In the interior of $\triangle ABC$ we take the arbitrary point $P$. Prove that the following inequality holds: $$\small c(\sin\angle CAP + \sin\angle CBP) + a(\sin\angle ABP +\sin\angle ACP) + b(\sin\angle BCP + \sin\angle BAP)\\ \le a + b + c$$

I tried to draw the distances from $P$ to the sides of the triangle and write the sines from the right angled triangles, but I couldn't get anything out of it. I saw that a case of equality is when the triangle is equilateral and $P$ is its center.

Can you help me?

$\endgroup$
  • $\begingroup$ Interesting inequality. Where does it come from? $\endgroup$ – ΑΘΩ Mar 14 '19 at 13:14
  • $\begingroup$ It is from the romanian publishment “Gazeta Matematica”. $\endgroup$ – Michael Goldberg Mar 14 '19 at 16:17
  • $\begingroup$ If you would be as kind as to tell us what edition of the Gazette that might be, we might be able to look things up ;) $\endgroup$ – ΑΘΩ Mar 14 '19 at 16:37
  • $\begingroup$ It is from the edition 10/2018, the number of the problem being S:L18.249 :) $\endgroup$ – Michael Goldberg Mar 14 '19 at 16:53
3
$\begingroup$

To simplify derivation introduce the notation: $$ BC=a,\quad AC=b,\quad AB=c,\quad \widehat{CAB}=\alpha, \widehat{ABC}=\beta,\quad \widehat{BCA}=\gamma;\\ \widehat{ABP}=\alpha_B,\quad\widehat{ACP}=\alpha_C,\quad \widehat{BAP}=\beta_A,\quad\widehat{BCP}=\beta_C,\quad \widehat{CAP}=\gamma_A,\quad\widehat{CBP}=\gamma_B. $$ Then the initial inequality can be written as: $$ \frac{a(\sin\alpha_B+\sin\alpha_C) +b(\sin\beta_A+\sin\beta_C)+c(\sin\gamma_A+\sin\gamma_B)}{a+b+c}\le1.\tag{*} $$ which can be proved as follows: $$\begin{align} &\frac{a(\sin\alpha_B+\sin\alpha_C) +b(\sin\beta_A+\sin\beta_C)+c(\sin\gamma_A+\sin\gamma_B)}{a+b+c}\\ &=\frac{\sin\alpha(\sin\alpha_B+\sin\alpha_C) +\sin\beta(\sin\beta_A+\sin\beta_C)+\sin\gamma(\sin\gamma_A+\sin\gamma_B)} {\sin\alpha+\sin\beta+\sin\gamma}\tag1\\ &=\frac{(\sin\beta\sin\beta_A+\sin\gamma\sin\gamma_A) +(\sin\alpha\sin\alpha_B+\sin\gamma\sin\gamma_B) +(\sin\alpha\sin\alpha_C+\sin\beta\sin\beta_C)} {\sin\alpha+\sin\beta+\sin\gamma}\tag2\\ &\le\frac{\sin\alpha+\sin\beta+\sin\gamma}{\sin\alpha+\sin\beta+\sin\gamma}=1\tag3. \end{align} $$

$(1)$: Substitution: $$a=2R\sin\alpha, \quad b=2R\sin\beta, \quad c=2R\sin\gamma.$$

$(2)$: Rearrangement.

$(3)$: Transformation of sine products to cosine differences and then from cosine sums to cosine products.
$$\begin{align} &\sin\beta\sin\beta_A+\sin\gamma\sin\gamma_A\\ &=\frac{\cos(\beta-\beta_A)-\cos(\beta+\beta_A)}2 +\frac{\cos(\gamma-\gamma_A)-\cos(\gamma+\gamma_A)}2\\ &=\frac{\cos(\beta-\beta_A)+\cos(\gamma-\gamma_A)}2 -\frac{\cos(\beta+\beta_A)+\cos(\gamma+\gamma_A)}2\\ &= \underbrace{\cos\frac{\beta+\gamma-\beta_A-\gamma_A}2}_{\ge0} \underbrace{\cos\frac{\beta-\gamma-\beta_A+\gamma_A}2}_{\le1} - \underbrace{\cos\frac{\beta+\gamma+\beta_A+\gamma_A}2}_{=0}\cos\frac{\beta-\gamma+\beta_A-\gamma_A}2\tag4\\ &\le \cos\frac{\beta+\gamma-\alpha}2=\cos\left(\frac\pi2-\alpha\right)=\sin\alpha, \end{align} $$ where we used $\beta_A+\gamma_A=\alpha$.


There may arise an interesting question when does the inequality $(\text{*})$ degenerate to equality?

It is easily seen from $(4)$ that this happens if and only if the following equations hold: $$ \begin {cases} \beta-\beta_A=\gamma-\gamma_A\\ \gamma-\gamma_B=\alpha-\alpha_B\\ \alpha-\alpha_C=\beta-\beta_C \end {cases}, $$ which together with $$ \begin {cases} \beta_A+\gamma_A=\alpha\\ \gamma_B+\alpha_B=\beta\\ \alpha_C+\beta_C=\gamma \end {cases} $$ implies: $$ \begin {cases} \beta_C=\gamma_B=\frac\pi2-\alpha\\ \gamma_A=\alpha_C=\frac\pi2-\beta\\ \alpha_B=\beta_A=\frac\pi2-\gamma \end {cases}. $$

Thus the equality holds if and only if the triangle $ABC$ is acute and $P$ is its circumcenter.

Note:

With the convention that the angles oriented oppositely to the direction towards the adjacent side are treated as negative, the inequality $(\text{*})$ becomes valid for the whole plane. Correspondingly the equality holds at the circumcenter of a triangle, regardless of its shape.

$\endgroup$
  • $\begingroup$ Thank you very much! $\endgroup$ – Michael Goldberg Mar 15 '19 at 14:58
  • $\begingroup$ @MichaelGoldberg You're welcome! $\endgroup$ – user Mar 15 '19 at 15:09
  • $\begingroup$ Great presentation! $\endgroup$ – Allawonder Mar 16 '19 at 10:28
  • $\begingroup$ @Allawonder Thank you! $\endgroup$ – user Mar 16 '19 at 10:38
  • 1
    $\begingroup$ A lovely solution! Just one remark though: the case of equality entails indeed the equations displayed in the final curly brace, however the conclusion on $P$ is not entirely correct. From $\sphericalangle{ABP}=\sphericalangle{BAP}$ one infers $|PA|=|PB|$ and the analogues, to the conclusion that $P$ is the circumcenter. The requirement that the triangle be acute is indeed valid. $\endgroup$ – ΑΘΩ Mar 21 '19 at 11:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.